2009
DOI: 10.1073/pnas.0912204106
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of phospholipase C β4 in thalamocortical relay nucleus leads to absence seizures

Abstract: Absence seizures are characterized by cortical spike-wave discharges (SWDs) on electroencephalography, often accompanied by a shift in the firing pattern of thalamocortical (TC) neurons from tonic to burst firing driven by T-type Ca 2؉ currents. We recently demonstrated that the phospholipase C ␤4 (PLC␤4) pathway tunes the firing mode of TC neurons via the simultaneous regulation of T-and L-type Ca 2؉ currents, which prompted us to investigate the contribution of TC firing modes to absence seizures. PLC␤4-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 39 publications
2
51
1
Order By: Relevance
“…Taken together, these findings suggest that spindle oscillations can be generated and propagated via any type of TC spike activity as long as TC neurons discharge spikes at an appropriate frequency. This conclusion differs from previous observations on the critical role of TC T-type channels in sleep delta waves (16) and paroxysmal SWDs (13,32,33), and leads us to suggest that the various TC oscillations may be generated through diverse mechanisms. Ca V 3.1 T-Type Channels in Spindles vs. SWDs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Taken together, these findings suggest that spindle oscillations can be generated and propagated via any type of TC spike activity as long as TC neurons discharge spikes at an appropriate frequency. This conclusion differs from previous observations on the critical role of TC T-type channels in sleep delta waves (16) and paroxysmal SWDs (13,32,33), and leads us to suggest that the various TC oscillations may be generated through diverse mechanisms. Ca V 3.1 T-Type Channels in Spindles vs. SWDs.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have found that Ca V 3.1 −/− mice are resistant to GABA B receptor agonist-induced SWDs (13), and that deletion of Ca V 3.1 completely suppresses or markedly reduces SWDs in genetic mouse models of absence seizures (35), implying that Ca V 3.1 T-type Ca 2+ channels play a crucial role in the genesis of SWDs. In contrast, the increased T-type Ca 2+ currents in TC neurons occur alongside the generation of SWDs and absence seizure phenotypes in transgenic or mutant mice (32,33). Our present findings support the hypothesis that Ca V 3.1 Ttype Ca 2+ channels are not an essential component in the generation of sleep spindles.…”
Section: Discussionsupporting
confidence: 82%
“…The PLCβ4 −/− mice exhibited mild absence seizures, as has been previously reported [26], with occasional spike-wave discharges (SWDs) in the EEG recordings (green vertical bars in the extended hypnogram plot in the upper panel in Fig. 1d).…”
Section: Resultssupporting
confidence: 68%
“…This result is in line with previous finding with a rat model with spontaneous absence seizure showing that SWDs are initiated in the facial region of the somatosensory cortex (Meeren et al 2002). Recently genetic studies have contributed to the understanding of generation of absence seizure in the molecular level, for instance, the ␣1G subunit of low-voltageactivated T-type Ca 2ϩ channels in thalamocortical relay neurons are involved in the genesis of absence seizure (Kim et al 2001); on the other hand, phospholipase C ␤4 in the thalamic reticular neuron conduces absence seizure (Cheong et al 2009). However, it is true that these genes have a role as modulator rather than exterminator or source for SWDs.…”
Section: Localization Of Absence Seizure Onset In Micementioning
confidence: 99%